Light conversion agricultural film for increasing yield of fruits and vegetables, and preparation method and application thereof

CN122878658APending Publication Date: 2026-10-09NORTHWEST NORMAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611141648.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-30
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0006]针对现有转光农膜存在的以下技术缺陷:有机转光剂光稳定性差且使用寿命短、稀土配合物成本高昂且资源稀缺、含镉铅量子点的重金属迁移风险限制其农业应用、有机相合成量子点涉及有毒溶剂且与聚合物基体相容性差导致团聚和透光率劣化、现有农膜普遍缺乏光质调控能力且透光率衰减剧烈,本发明提供一种用于果蔬增产的转光农膜及其制备方法和应用

Benefits of technology

(1)本发明采用无镉AgInS2三元量子点作为转光材料,不含镉、铅等重金属元素,从源头消除了重金属向土壤和作物迁移的风险,解决了传统含镉量子点无法应用于农业食品链的技术瓶颈。β-环糊精配体源自天然原料,具有良好的生物可降解性和环境相容性,整个制备过程在水相中进行,不使用十八烯、油胺、三辛基氧化膦等有毒有机溶剂,属于绿色环保工艺。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122878658A_ABST
    Figure CN122878658A_ABST
Patent Text Reader

Abstract

The application discloses a light-conversion agricultural film for increasing yield of fruits and vegetables and a preparation method and application thereof, and belongs to the technical field of agricultural functional film materials. The light-conversion agricultural film comprises an ethylene-vinyl acetate copolymer base and AgInS2 quantum dots dispersed in the base, the AgInS2 quantum dots are modified by mercapto diethylene triamine and beta-cyclodextrin as a ligand, the emission wavelength is 650-850 nm, the particle size is 4-8.5 nm, and the mass ratio of the ethylene-vinyl acetate copolymer to the AgInS2 quantum dots is 5:1-20:1. The application further discloses a preparation method of the light-conversion agricultural film, the AgInS2 quantum dots are obtained through aqueous synthesis, and then a tetrahydrofuran solution of the ethylene-vinyl acetate copolymer is mixed to prepare a film. When the light-conversion agricultural film is used as a greenhouse covering film, short-wavelength visible light in a 400-600 nm wave band in a solar spectrum can be converted into red light with a wavelength of 630-700 nm required by photosynthesis of plants, the growth cycle is shortened by 5-8 days when fruits and vegetables are planted under the covering film, and the yield is increased by 15%-30%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of agricultural functional film materials technology, specifically relating to a light-converting agricultural film for increasing fruit and vegetable yields, its preparation method, and its application. Background Technology

[0002] Light is the energy source for plant photosynthesis and has a decisive impact on plant growth, development, morphogenesis, yield, and quality. However, the effects of radiation energy in different bands of the solar spectrum on plants vary significantly. Ultraviolet light (wavelength <400 nm) has a significant inhibitory effect on plant growth and development, including reducing leaf area, inhibiting hypocotyl elongation, decreasing photosynthetic efficiency, and even causing DNA damage and apoptosis. Blue light (400–500 nm) and red light (630–700 nm) are the most effectively utilized spectral regions for plant photosynthesis and are key energy sources driving photosynthesis. Therefore, how to convert the ultraviolet light in the solar spectrum, which is neither beneficial nor harmful to crops, into photosynthetically effective radiation has always been a research hotspot in the field of protected agriculture.

[0003] Photoluminescent agricultural films are a type of functional agricultural covering material that converts ultraviolet or short-wavelength visible light in the solar spectrum into red or blue light required for plant photosynthesis by adding photoluminescent materials to a polymer matrix. Currently, commercially available photoluminescent agricultural films mainly use organic photoluminescent agents or rare earth complexes as light conversion materials. The above technical routes have revealed the following problems in practical applications: (1) Organic photoluminescent agents have poor photostability and are prone to photobleaching and photodegradation under strong outdoor light. The light conversion efficiency decreases significantly with the use time, and the effective service life is generally less than 6 months; (2) Although rare earth complexes have good photostability, the preparation process is complicated and the cost is high. In addition, some rare earth elements are scarce, which limits their large-scale promotion and application; (3) The emission spectrum of existing photoluminescent materials does not match the spectrum of plant photosynthesis, and the light energy conversion efficiency is low.

[0004] Quantum dots, with their excellent photoluminescence properties, size-tunable emission wavelengths, and high quantum yield, show great promise for applications in photoelectric conversion and bioimaging. However, applying quantum dot technology to agricultural films still faces key bottlenecks: traditional quantum dots often contain heavy metals such as cadmium and lead, posing a potential risk of heavy metal migration and directly limiting their application in the agri-food chain. Furthermore, the synthesis of existing quantum dots typically employs a high-temperature hot-injection method with organic phases, involving toxic organic solvents such as octadecene, oleylamine, and trioctylphosphine oxide, as well as complex post-processing steps. This not only increases production costs and environmental pollution risks but also makes it difficult to disperse the hydrophobic ligands coated on the quantum dot surface in aqueous media, resulting in poor compatibility with hydrophilic polymer matrices. This leads to the easy aggregation of quantum dots in the agricultural film matrix, severely degrading the film's transmittance and mechanical properties. Therefore, there is an urgent need to develop a quantum dot light-conversion material and its agricultural film preparation technology that combines environmental friendliness, high light conversion efficiency, and good compatibility with polymer matrices.

[0005] Existing agricultural films have limited functions, mostly providing only basic heat preservation and covering, lacking the ability to regulate light quality and convert ultraviolet light in the solar spectrum into useful light energy for crop photosynthesis. Furthermore, commercially available agricultural films generally suffer from a significant decrease in light transmittance, typically exceeding 30% after three months of use, severely impacting lighting conditions for crops inside greenhouses and directly leading to yield reduction. In addition, while cadmium-free quantum dots synthesized in aqueous phase possess excellent environmental friendliness and optical properties, efficiently and uniformly dispersing them in agricultural film matrix materials such as ethylene-vinyl acetate copolymers, and ensuring that the prepared light-converting agricultural film possesses high light transmittance, high light conversion efficiency, and long-term stability, remains a pressing technical challenge. Summary of the Invention

[0006] To address the following technical shortcomings of existing light-converting agricultural films: poor photostability and short lifespan of organic light-converting agents; high cost and scarcity of rare earth complexes; heavy metal migration risks of cadmium- and lead-containing quantum dots limiting their agricultural application; the use of toxic solvents in the synthesis of quantum dots in organic phases, leading to agglomeration and deterioration of light transmittance due to poor compatibility with polymer matrices; and the general lack of light quality regulation capabilities and severe attenuation of light transmittance in existing agricultural films, this invention provides a light-converting agricultural film for increasing fruit and vegetable yields, its preparation method, and its application.

[0007] To achieve the above objectives, the present invention adopts the following technical solution: The phototransfer agricultural film of the present invention comprises an ethylene-vinyl acetate copolymer matrix and AgInS2 quantum dots dispersed in the matrix.

[0008] The AgInS2 quantum dots use β-cyclodextrin modified with thiolized diethylenetriamine as a ligand, emit wavelengths of 650 nm to 850 nm, have particle sizes of 4 nm to 8.5 nm, an absolute fluorescence quantum yield of 23.5%, and an average fluorescence lifetime of 604.38 ns.

[0009] The mass ratio of the ethylene-vinyl acetate copolymer to the AgInS2 quantum dots is 5:1 to 20:1; the thickness of the light-converting agricultural film is 0.05 mm to 0.15 mm.

[0010] Furthermore, the mass ratio of the ethylene-vinyl acetate copolymer to the AgInS2 quantum dots is 10.6:1.

[0011] The AgInS2 quantum dots are cadmium-free ternary quantum dots prepared by aqueous synthesis. Their surfaces are coated with β-cyclodextrin ligands modified with thiolated diethylenetriamine, which endows the quantum dots with water dispersibility and interfacial compatibility with the EVA matrix.

[0012] The method for preparing the light-converting agricultural film of the present invention includes the following steps: (a) Dissolve the β-cyclodextrin modified with thiolized diethylenetriamine in water, add ammonium citrate, adjust the pH to neutral, add an aqueous solution of InCl3, readjust the pH to neutral, and heat to reflux temperature; Under reflux, aqueous solutions of AgNO3 and Na2S are sequentially injected into the reaction system; the citrate ions generated by the ionization of ammonium citrate react with In... 3+ Coordination forms the first complex; after deprotonation, the β-cyclodextrin modified with thiolized diethylenetriamine reacts with Ag. + Coordination forms a second complex; the first and second complexes thermally decompose at reflux temperature to release In 3+ and Ag + The released In 3+ and Ag + With S 2- Nucleation and growth occur, with β-cyclodextrin modified with thiolized diethylenetriamine serving as the sole end-capped ligand coating the surface of AgInS2 quantum dots to obtain an aqueous dispersion of AgInS2 quantum dots. The AgInS2 quantum dot aqueous dispersion was subjected to precipitation separation, washing, and drying to obtain AgInS2 quantum dot powder. (ii) The ethylene-vinyl acetate copolymer is dissolved in tetrahydrofuran and mixed with the aqueous dispersion of the AgInS2 quantum dot powder. The miscibility of tetrahydrofuran and water is used to uniformly disperse the AgInS2 quantum dots in the ethylene-vinyl acetate copolymer matrix. The solvent is removed, a film is formed and dried to obtain the light-converting agricultural film.

[0013] Furthermore, the reflux temperature is 100℃~120℃, and the AgNO3 aqueous solution and Na2S aqueous solution are injected and then refluxed for 20min~60min.

[0014] Furthermore, the molar ratio of AgNO3 to the β-cyclodextrin modified with thiolated diethylenetriamine is 1:4 to 1:14.

[0015] Furthermore, the molar ratio of AgNO3 to InCl3 is 1:3 to 1:5.

[0016] Furthermore, the precipitation separation includes adding the AgInS2 quantum dot aqueous dispersion to anhydrous ethanol to precipitate the precipitate, followed by centrifugation and washing the precipitate with acetone.

[0017] Further, the ratio of the ethylene-vinyl acetate copolymer to the tetrahydrofuran is 1g:5mL to 1g:15mL; the mass ratio of the ethylene-vinyl acetate copolymer to the AgInS2 quantum dots is 10.6:1; the solvent removal is carried out by evaporation at room temperature for 18h to 36h; and the drying is carried out by vacuum drying at 40°C to 60°C for 12h to 24h.

[0018] The application of the light-converting agricultural film of the present invention in facility agriculture, wherein the light-converting agricultural film is used as a greenhouse covering film, converting short-wavelength visible light in the 400~600 nm band of the solar spectrum into red light with a wavelength of 630~700 nm.

[0019] The light conversion mechanism of the light-converting agricultural film is as follows: AgInS2 quantum dots absorb short-wavelength visible light in the 400-600 nm band of the solar spectrum and emit red light (main peak 755 nm) with a wavelength matching the spectrum of plant photosynthesis through photoluminescence effect. This converts high-energy photons with low photosynthetic utilization efficiency into light energy to drive photosynthesis, thereby increasing the photosynthetically effective radiation intensity in the greenhouse, improving the photosynthetic efficiency of crops, accelerating the accumulation of organic matter, and shortening the crop growth cycle and increasing yield.

[0020] Furthermore, the light-converting agricultural film is used for the cultivation of fruits and vegetables, including tomatoes, peppers, cucumbers, strawberries, radishes, bok choy, or corn.

[0021] Compared with the prior art, the present invention has the following beneficial effects: (1) This invention uses cadmium-free AgInS2 ternary quantum dots as the light-converting material. It does not contain heavy metal elements such as cadmium and lead, thus eliminating the risk of heavy metal migration to soil and crops from the source and solving the technical bottleneck that traditional cadmium-containing quantum dots cannot be applied to the agricultural food chain. The β-cyclodextrin ligand is derived from natural raw materials and has good biodegradability and environmental compatibility. The entire preparation process is carried out in the aqueous phase and does not use toxic organic solvents such as octadecene, oleylamine, and trioctylphosphine oxide, which is a green and environmentally friendly process.

[0022] (2) The optimal excitation wavelength of AgInS2 quantum dots is 540 nm, the absorption spectrum covers the 400-600 nm band, and the emission wavelength is 650-850 nm (with the main peak at 755 nm), which highly matches the absorption spectrum of red light for plant photosynthesis. The absolute fluorescence quantum yield of the quantum dots reaches 23.5%, which can efficiently convert short-wavelength visible light in the 400-600 nm band of the solar spectrum into photosynthetically active radiation, significantly improving the intensity of photosynthetically active radiation in the greenhouse, and effectively solving the problem of insufficient matching between the emission spectrum of existing light-converting materials and the needs of plant photosynthesis. Field trials show that after covering crops with the light-converting agricultural film of this invention, the chlorophyll a and chlorophyll b contents of crops increased by 65%-102% and 62%-120% respectively compared with the control ordinary PE agricultural film.

[0023] (3) The present invention endows AgInS2 quantum dots with excellent water dispersibility by designing β-cyclodextrin ligands modified with thiolized diethylenetriamine; at the same time, by utilizing the miscibility of tetrahydrofuran and water, the aqueous dispersion of quantum dots synthesized in the aqueous phase is uniformly mixed with the THF solution of EVA, realizing the monodisperse state of quantum dots in the EVA matrix at the nanoscale (particle size 4~8.5 nm) without obvious agglomeration, thereby ensuring that the composite agricultural film has a high visible light transmittance of 87.5%, overcoming the defect of the transmittance degradation caused by the agglomeration of quantum dots in the prior art.

[0024] (4) AgInS2 quantum dots are inorganic semiconductor nanocrystals with excellent photostability, unlike organic light-converting agents that are prone to photobleaching. Experiments show that the fluorescence intensity of the light-converting agricultural film of the present invention does not decrease significantly under continuous ultraviolet irradiation, and the fluorescence intensity does not decrease significantly during the 16-day storage period. It can maintain stable light-converting performance for a long time, and its effective service life is far longer than that of organic light-converting agent products.

[0025] (5) Field comparative trials show that the growth cycle of crops such as radishes, corn, and Shanghai bok choy covered by the light-converting agricultural film of this invention is shortened by 5 to 8 days compared with ordinary PE agricultural film, the yield is increased by 15% to 30%, and the sugar content and marketability are significantly improved. The light-converting agricultural film effectively converts the short-wavelength visible light, which was originally less efficient for crop utilization, into red light that is more efficient for photosynthesis, thus realizing the active yield-increasing function upgrade of "turning harm into benefit and waste into treasure".

[0026] (6) The synthesis of AgInS2 quantum dots in this invention is completed in one pot in an aqueous phase, without the need for high temperature, high pressure and inert gas protection. The reaction conditions are mild (reflux temperature 100°C~120°C, reaction time 20~60 min). The post-treatment only requires ethanol precipitation and acetone washing. The process is simple and easy to scale up. The preparation of EVA composite film adopts conventional solution casting method, without the need for special equipment. It is compatible with existing agricultural film production processes and is easy to promote industrialization. Attached Figure Description

[0027] Figure 1 The 1H NMR spectrum of 6-OTs-β-CD (room temperature, DMSO-d6).

[0028] Figure 2 The mass spectrometry of 6-OTs-β-CD.

[0029] Figure 3 The NMR spectrum of DTCD is 1H NMR (room temperature, DMSO-d6).

[0030] Figure 4 This is the mass spectrometry of DTCD.

[0031] Figure 5 The 1H NMR spectrum of SH-DTCD (room temperature, D2O).

[0032] Figure 6 This is the mass spectrometry of SH-DTCD.

[0033] Figure 7 This is a schematic diagram illustrating the formation mechanism of DTCD-AIS QDs in this invention.

[0034] Figure 8 The following are the (a) X-ray diffraction pattern and (b) chemical composition analysis spectrum of the DTCD-AIS QDs of this invention.

[0035] Figure 9 This is a full X-ray photoelectron spectroscopy (XPS) scan of the DTCD-AIS QDs of this invention.

[0036] Figure 10 The high-resolution XPS spectra of C1s, O1s, Ag3d, In3d, and S2p of the DTCD-AIS QDs of this invention are shown.

[0037] Figure 11 (a) TEM image of DTCD-AISQDs (scale bar: 50 nm), bottom left: HR-TEM image and lattice spacing (scale bar: 5 nm); (b) histogram of particle size distribution, right: path diagram of QDs illuminated by laser pointer (sunlight).

[0038] Figure 12This is the EDS energy spectrum and surface distribution diagram of C, N, O, S, Ag, and In elements of the DTCD-AIS QDs of this invention.

[0039] Figure 13 These are two-dimensional and three-dimensional atomic force microscopy (AFM) images of the DTCD-AIS QDs of this invention.

[0040] Figure 14 The ultraviolet absorption and fluorescence spectra of the DTCD-AIS QDs of this invention are shown in the illustration: a photograph of the sample under sunlight / ultraviolet light. Figure 15 The graph shows the fluorescence lifetime decay trend and fitting curve of the DTCD-AIS QDs of this invention.

[0041] Figure 16 (a) Fluorescence curves of DTCD-AIS QDs measured every two days from 0 to 16 days in aqueous solution; (b) Normalized bar graph of fluorescence intensity of DTCD-AIS QDs at different placement times in aqueous solution; (c) Fluorescence micrographs of DTCD-AIS QDs after continuous irradiation in the red channel for 6, 12, and 18 hours (scale bar: 10 μm).

[0042] Figure 17 (a) Zeta potential test diagram of the DTCD-AIS QDs of this invention, and (b) TEM images after 0 days, 5 days, 10 days and 15 days.

[0043] Figure 18 The thermogravimetric analysis (TGA) and differential thermogravimetric analysis (DTG) curves of the DTCD-AIS QDs of this invention are shown.

[0044] Figure 19 The image shows the fluorescence of the DTCD-AIS QDs / EVA phototransformation film of this invention under 365 nm ultraviolet light irradiation (left) and a control image of ordinary EVA film (right).

[0045] Figure 20 These are comparative photos of corn germination under the same day when the DTCD-AIS QDs / EVA light-converting agricultural film of the present invention (experimental group: (b)) and commercially available ordinary PE agricultural film (control group: (a)) were covered. Detailed Implementation

[0046] The present invention will be further described below with reference to embodiments, but the present invention is not limited to the following embodiments. Those skilled in the art can make various modifications and changes without departing from the concept of the present invention, and these modifications and changes all fall within the protection scope of the present invention.

[0047] Example 1 I. Preparation of DTCD-AIS QDs like Figure 7 As shown, the aqueous green synthesis of water-soluble SH-DTCD-terminated AgInS2 quantum dots (DTCD-AIS QDs) is as follows: 1. Synthesis of thiol mono(6-amino-6-deoxy)-β-cyclodextrin (SH-DTCD) 1.1 Synthesis of 6-p-methylbenzenesulfonyl-6-deoxy-β-cyclodextrin (6-OTs-β-CD) β-cyclodextrin (β-CD, 10 g, 8.8 mmol) and sodium hydroxide solution (200 g, 0.75 mol•L) were added to a reaction vessel placed in a water bath at 0-5℃. -1 After thorough stirring and dissolution, p-toluenesulfonyl chloride (TsCl, 3.36 g, 17.6 mmol) was slowly added, and the reaction was maintained at 0-5℃ for 5 h. Unreacted p-toluenesulfonyl chloride was separated from the reaction mixture by filtration. The filtrate was adjusted to pH 7 with 10% hydrochloric acid and refrigerated at 0℃ for 10 h. The crude product was then filtered to obtain the crude product. The crude product was then subjected to hot filtration in boiling water to remove impurities. The filtrate was refrigerated at 0℃ for 12 h, filtered, and dried at 60℃ for 12 h to obtain the product 6-p-methylbenzenesulfonyl-6-deoxy-β-CD (6-OTs-β-CD), with a yield of 48%.

[0048] 1H NMR (600 MHz, DMSO-d6) δ: 7.72 (d, J=7.8Hz, 2H), 7.40 (d, J=7.9Hz, 2H), 5.75-5.66 (m, 14H), 4.85-4.77 (m, 7H), 4.52-4.43 (m, 6H), 4.36 (s,1H), 3.63-3.47 (m, 33H), 3.27 (d, J=9.2 Hz, 7H), 2.40 (s, 3H). ESI-MS: m / z calcd for C 49 H 76 O 37 NaS [M+Na] + , 1311.3684, found:1311.3663. The 1H NMR spectrum of this product is shown below. Figure 1 Mass spectrometry Figure 2 .

[0049] 1.2 Synthesis of mono(6-amino-6-deoxy)-β-cyclodextrin (DTCD) The prepared 6-OTs-β-CD (2.0 g, 1.55 mmol), potassium iodide (KI, 0.025 g, 0.15 mmol), and diethylenetriamine (0.54 mL, 5 mmol) were added to methylpyrrolidone (NMP, 5 mL). The reaction was stopped after stirring at 70 °C for 8 h, and the product turned pale yellow. The reaction product was cooled to room temperature and precipitated in anhydrous ethanol (100 mL). The crude product obtained after filtration was repeatedly washed with ethanol. The final residue was dissolved in a mixed solution of water and methanol (V water:V methanol = 3:1), and the precipitate was repeatedly dissolved and precipitated three times with acetone. After vacuum drying, a white solid product, mono(6-amino-6-deoxy)-β-cyclodextrin (DTCD), was obtained, with a yield of 40%.

[0050] 1H NMR (600 MHz, DMSO) δ: 9.32 (s, 2H), 5.78 (d, 7H), 4.76 (t, 7H), 4.39 (s, 7H), 3.92 (m, 27H), 3.39 (m, 12H), 3.34 (m, 7H), 2.81 (m, 14H), 1.49(m, 2H) ppm. ESI-MS: m / z calcd for C 46 H 82 O 34 N3[M+H] + , 1220.4780, found: 1220.4780. The 1H NMR spectrum of this product is shown below. Figure 3 Mass spectrometry Figure 4 .

[0051] 1.3 Synthesis of Thiol Mono(6-amino-6-deoxy)-β-cyclodextrin (SH-DTCD) 64 mg of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloric acid and 38 mg of N-hydroxythiosuccinimide were added to 40 mL of N,N-dimethylformamide. After stirring at room temperature for 10 min, 53 mg of 3-mercaptopropionic acid was added, and the mixture was stirred for 30 min. The prepared DTCD solution (1 mL, 300 mg / mL) was then added. -1 DMF was added dropwise while stirring continuously for 6 hours. The crude product was repeatedly centrifuged and precipitated with anhydrous ethanol, and then vacuum dried to obtain a light yellow product SH-DTCD, with a yield of 37%. SH-DTCD is β-cyclodextrin modified with thiolated diethylenetriamine.

[0052] 1H NMR (600 MHz, D2O) δ: 9.32 (s, 2H), 5.78 (d, 7H), 4.76 (t, 7 H), 4.39 (s, 7H), 3.92 (m, 27H), 3.42 (m, 12H), 3.34(m, 7H), 2.81 (m, 14H), 1.49(m, 2H) ppm. ESI-MS: m / z calcd for C 49 H 85 O 36 N3S [M+Cl] - , 1358.4659, found: 1358.4665. The 1H NMR spectrum of this product is shown below. Figure 5 Mass spectrometry Figure 6 .

[0053] 2. Synthesis of DTCD-AIS QDs Accurately weigh SH-DTCD (2.01 g, 1.50 mmol) into a 100 mL three-necked flask and add 20 mL of deionized water. Then, add ammonium citrate (126 mg, 0.517 mmol) to the flask, and adjust the pH of the mixture to 7.5 with a 5 mol / L ammonia solution. Next, add 0.5 mL of a 1 mol / L indium trichloride (InCl3) solution, which immediately forms a precipitate. To ensure system stability, readjust the pH of the suspension to 7.5 with a 5 mol / L ammonia solution. The reaction mixture is then heated to 120 °C and kept boiling. Under this reflux condition, rapidly add 1.25 mL of a 0.1 mol / L AgNO3 aqueous solution, followed immediately by 0.625 mL of a 1 mol / L Na2S aqueous solution. A significant color change is observed in the reaction mixture, from transparent to reddish-brown. The reaction continues at a constant boil for 30 min. Immediately after the reaction is complete, perform hot filtration to remove insoluble impurities, and carefully collect the filtrate. The collected filtrate was slowly poured into 100 mL of anhydrous ethanol under continuous stirring, forming a large amount of brown precipitate. The suspension containing the precipitate was centrifuged at 6000 r / min for 5 min to separate the solid phase. The resulting precipitate was washed three times with acetone to remove residual impurities. Finally, the washed precipitate was freeze-dried to obtain a reddish-brown solid DTCD-AIS QDs powder, which was stored for later use.

[0054] II. DTCD-AIS QDs Structural Characterization 1. Crystal structure analysis (XRD) and chemical composition analysis (FTIR) The crystal structure of DTCD-AIS QDs was analyzed using X-ray diffraction. For example... Figure 8 As shown in Figure a, the XRD pattern of DTCD-AIS QDs shows three distinct broad diffraction peaks located at 28.4°, 44.5°, and 48.0°, corresponding to the (121), (320), and (123) crystal planes of the orthorhombic AgInS2 (JCPDS No. 25-1328), indicating that the quantum dot crystal structure is well maintained after SH-DTCD modification. The broad and diffuse characteristics of the diffraction peaks reflect that DTCD-AIS QDs have a small size and a wide size distribution.

[0055] like Figure 8 As shown in b, 3600~3000cm -1 The absorption peak at 3000~2900 cm⁻¹ is due to the stretching vibration of the hydroxyl group (-OH). -1 2500~2600cm -1 and 1750cm -1 The absorption peaks at 1150 cm⁻¹ are attributed to the methylene (-CH₂-), thiol (-SH), and carbonyl (C=O) groups in the ester group, respectively. -1 1080cm -1 and 1030cm -1 The peaks at the specified locations are attributed to the characteristic absorptions of the COC, CC, and CO bonds in the ligands, respectively. Notably, the -SH characteristic peak almost disappears in the DTCD-AIS QDs spectrum, indicating that the synthesis of AgInS2QDs depends on the coordination of the thiol group in the DTCD.

[0056] 2. Elemental composition and valence state analysis (XPS) X-ray photoelectron spectroscopy was used to analyze the elemental composition and valence states of DTCD-AIS QDs. Figure 9 As shown, the characteristic signal peaks of C 1s, N 1s, O 1s, S 2p, In 3d and Ag 3d were clearly visible in the full spectrum scan results, with binding energies at 285, 400, 532, 163, 445 and 367 eV, respectively.

[0057] like Figure 10 As shown, the C 1s high-resolution spectrum fitted with four peaks: 287.9 ​​eV (C=O bond), 286.5 eV (CO bond), 285.9 eV (CC bond), and 284.7 eV (CH bond); the N 1s high-resolution spectrum fitted with three peaks: 401.5 eV (-NH-C(O)- bond), 399.7 eV (NC), and 399.2 eV (NH), attributed to the nitrogen element on diethylenetriamine. The Ag3d core energy level is composed of Ag 3d 3 / 2 (373.5 eV) and Ag 3d 5 / 2The peaks at 367.4 eV consist of two peaks, with no shoulder peak appearing near 368.2 eV and exhibiting a symmetrical distribution, confirming the presence of Ag. + Its oxidation state is +1 and elemental silver does not exist. In 3d 5 / 2 (444.5 eV) and In 3d 3 / 2 (452.1 eV) confirmed In 3+ The oxidation state of sulfur was determined. XPS spectroscopy of the S2p level confirmed that sulfur exists in the -2 oxidation state.

[0058] 3. Morphological characterization (TEM) The quantum dots exhibit a regular spherical shape and good monodispersity, with a particle size distribution in aqueous solution between 4 and 8.5 nm. Figure 11 (b) The average particle size is approximately 5.67 nm, consistent with the results obtained from XRD analysis. Figure 11 The illustration clearly shows the lattice fringes of the quantum dots, with a plane spacing of approximately 3.14 Å, thus revealing the crystal structure characteristics of DTCD-AIS QDs. Furthermore, the clear lattice edges indicate that the crystal structure of AgInS2QDs did not undergo significant changes after encapsulation with oligosaccharide ligands.

[0059] 4. EDS energy dispersive spectroscopy analysis like Figure 12 As shown, C, O, Ag, In and S elements were detected in DTCD-AIS QDs, and C, O, Ag, In and S elements were uniformly distributed throughout the sample, confirming that DTCD was successfully coated on the surface of AgInS2QDs.

[0060] 5. Characterization by atomic force microscopy (AFM) The surface morphology and three-dimensional structure of DTCD-AIS QDs were characterized using atomic force microscopy. Figure 13 As shown, the two-dimensional and three-dimensional AFM images clearly demonstrate the uniform distribution of quasi-spherical nanoparticles on the substrate, with most individual quantum dots having a vertical dimension of less than 20 nm, consistent with the size range measured by TEM and DLS.

[0061] III. Performance Evaluation of DTCD-AIS QDs 1. Ultraviolet-Visible Absorption Spectroscopy and Fluorescence Spectroscopy The optical properties of DTCD-AIS QDs in aqueous solution were determined using a UV-Vis spectrophotometer and a fluorescence spectrometer. For example... Figure 14As shown, DTCD-AIS QDs exhibit strong absorption in the 400–600 nm range, mainly due to the absorption contribution of the thiolated ligands. The UV-Vis absorption spectrum shows a broad absorption band in the 400–1000 nm range without any obvious characteristic absorption peaks, indicating that DTCD-AIS QDs possess a broad-spectrum absorption capability covering the visible light region. At the optimal excitation wavelength of 540 nm, DTCD-AIS QDs emit bright near-infrared fluorescence at 755 nm. Figure 14 The illustration shows photographs of the sample under sunlight and ultraviolet light.

[0062] 2. Fluorescence quantum yield and fluorescence lifetime The absolute fluorescence quantum yield and average fluorescence lifetime of DTCD-AISQDs in aqueous solution were determined using steady-state / transient fluorescence spectroscopy. (See attached image) Figure 15 As shown in Table 1, the absolute fluorescence quantum yield of DTCD-AIS QDs is 23.5%, and the average fluorescence lifetime is 604.38 ns.

[0063] Table 1 Optical parameters of DTCD-AIS QDs Note: λ ex , λ em , , Ф f These represent the excitation wavelength, emission wavelength, fluorescence lifetime, confidence factor, and quantum yield, respectively.

[0064] 3. Stability (1) Optical stability like Figure 16 As shown in ab, the fluorescence intensity of DTCD-AISQDs did not show a significant decrease during the storage period of 0 to 16 days, indicating its good fluorescence stability in aqueous solution. Furthermore, the photostability of DTCD-AISQDs under continuous light source irradiation was verified. Figure 16 c). After continuous ultraviolet irradiation for 18 hours, its fluorescence intensity did not decrease significantly, indicating that it has good photostability.

[0065] (2) Structural and dimensional stability like Figure 17 As shown in figure a, the Zeta potential of DTCD-AIS QDs is -23.3 mV, indicating its good stability in solution. Furthermore, from... Figure 17 As can be seen, after 15 days, the quantum dot still maintains a regular spherical shape with an average diameter of about 5.70 nm and good dispersion, which fully demonstrates its size stability.

[0066] (3) Thermal stability The thermal stability of DTCD-AIS QDs was investigated using thermogravimetric analysis (TGA) and differential thermogravimetric analysis (DTG). The corresponding results are shown in [Figure number missing]. Figure 18 The thermogravimetric analysis (TGA) curves show that the quantum dots begin to thermally decompose at approximately 150℃. At 600℃, the mass retention rate is approximately 75%, and at approximately 1600℃, the mass retention rate drops to 50%, indicating that the safe operating temperature upper limit of the prepared quantum dots is approximately 150℃. The DTG curves show significant endothermic peaks near 630℃ and 780℃, and these characteristic temperatures are in good agreement with the thermogravimetric behavior observed in the TGA analysis. In conclusion, DTCD-AIS quantum dots maintain good structural integrity over a wide temperature range of 200℃ to 600℃.

[0067] Example 2 Preparation of DTCD-AIS QDs / EVA conversion film for agricultural use: EVA particles were dissolved in tetrahydrofuran at a ratio of 1 g:10 mL and magnetically stirred at room temperature until completely dissolved to obtain a clear and transparent EVA-THF solution. The DTCD-AIS QDs powder prepared in Example 1 was dispersed in deionized water at a mass ratio of EVA to DTCD-AIS QDs of 10.6:1 and ultrasonically dispersed for 15 min to obtain a uniform quantum dot aqueous dispersion.

[0068] Under stirring conditions at room temperature, the quantum dot aqueous dispersion was slowly added dropwise to the EVA-THF solution, and stirring was continued for 30 minutes until homogeneous. The mixture was then slowly poured into a 20 cm × 20 cm square horizontal glass mold, and the mold was gently shaken to level the liquid surface. The mold was then placed in a fume hood for evaporation at room temperature for 24 hours. Utilizing the miscibility of tetrahydrofuran with water, the quantum dots were uniformly formed into a film with the solvent and stably dispersed in the EVA matrix. The formed film was transferred to a vacuum drying oven and dried at 50 °C for 12 hours to constant weight, yielding a DTCD-AIS QDs / EVA photochemical agricultural film with a thickness of approximately 0.08 mm.

[0069] As attached Figure 19 As shown, the obtained DTCD-AIS QDs / EVA photoluminescent film emits bright red fluorescence under 365 nm ultraviolet light irradiation (left), while the ordinary EVA film does not emit fluorescence under the same conditions (right), indicating that quantum dots have been successfully loaded into the EVA matrix and maintain good luminescence performance.

[0070] Example 3 Verification of the growth-promoting effect of light-transfer agricultural film in the field: Experimental Design: Two greenhouses with identical conditions were constructed, one covered with DTCD-AISQDs / EVA light-converting agricultural film prepared in Example 5 (experimental group) and the other with commercially available ordinary PE agricultural film (control group). Thick-stemmed corn, thin-stemmed corn, radish, and Shanghai bok choy seedlings were planted in both greenhouses, with identical planting density, water and fertilizer management, and temperature and humidity control. Observations were recorded continuously for 60 days from the date of transplanting.

[0071] Chlorophyll content determination: The chlorophyll a and chlorophyll b contents of the leaves of each crop were determined by spectrophotometry. As shown in Table 2, the chlorophyll a and chlorophyll b contents of the experimental groups were significantly higher than those of the control group. Specifically, the chlorophyll a content of coarse-stemmed maize increased from 14.14 μg•mL in the control group. -1 Increased to 28.55 μg•mL in the experimental group -1 (Increased by 102%), chlorophyll b content increased from 3.64 μg•mL -1 Increased to 7.98 μg•mL -1 (Increased by 119%); the chlorophyll a content of radishes increased from 9.97 μg•mL in the control group. -1 Increased to 19.09 μg•mL in the experimental group. -1 (Increased by 91%), chlorophyll b content increased from 2.43 μg•mL -1 Increased to 4.34 μg•mL -1 (Increased by 79%); the chlorophyll a content of Shanghai bok choy increased from 16.47 μg•mL in the control group. -1 Increased to 27.64 μg•mL in the experimental group -1 (68% increase), chlorophyll b content increased from 4.11 μg•mL -1 Increased to 6.67 μg•mL -1 (62% increase).

[0072] The aboveground and underground lengths of all crops in the experimental groups were superior to those in the control group. For example, the aboveground length of thick-stemmed maize increased from 102.0 mm to 135.0 mm (a 32% increase), and the underground length increased from 123.0 mm to 140.0 mm (a 14% increase); the aboveground length of radish increased from 169.0 mm to 184.0 mm (a 9% increase), and the underground length increased from 140.0 mm to 149.0 mm (a 6% increase); and the aboveground length of Shanghai bok choy increased from 205.0 mm to 294.0 mm (a 43% increase).

[0073] Table 2. Chlorophyll content and growth indicators of various crops under different agricultural film coverings. Observe germination status: such as Figure 20As shown, when observing corn germination on the same day, the germination rate and seedling growth of the experimental group (b) were significantly better than those of the control group (a).

[0074] In summary, when the above crops were covered with the DTCD-AIS QDs / EVA light-converting agricultural film prepared according to this invention, radishes showed the most significant response, while Shanghai bok choy yielded the greatest aboveground portion benefit, with chlorophyll increase far exceeding morphological indicators. This indicates that the light-converting agricultural film of this invention significantly enhances crop photosynthetic efficiency by efficiently converting short-wavelength visible light in the 400-600 nm band of the solar spectrum into photosynthetically active radiation (main peak 755 nm red light), achieving significant yield increases and earlier maturity.

Claims

1. A light-converting agricultural film for increasing fruit and vegetable yield, characterized in that: The photopolymer agricultural film is composed of an ethylene-vinyl acetate copolymer matrix and AgInS2 quantum dots uniformly dispersed therein, wherein the mass ratio of the ethylene-vinyl acetate copolymer to the AgInS2 quantum dots is 5:1 to 20:1; the AgInS2 quantum dots are prepared by an aqueous green synthesis method using β-cyclodextrin modified with thiolated diethylenetriamine as a ligand. The thickness of the light-converting agricultural film is 0.05 mm to 0.15 mm.

2. The light-converting agricultural film according to claim 1, characterized in that, The mass ratio of the ethylene-vinyl acetate copolymer to the AgInS2 quantum dots is 10.6:

1.

3. A method for preparing the light-converting agricultural film as described in claim 1 or 2, characterized in that, Includes the following steps: (1) Dissolve the β-cyclodextrin modified with mercaptodiethylenetriamine in water, add ammonium citrate, adjust the pH to neutral, add an aqueous solution of InCl3, readjust the pH to neutral, and heat to reflux temperature; Under reflux, aqueous solutions of AgNO3 and Na2S are sequentially injected into the reaction system. The citrate ions generated by the ionization of ammonium citrate react with In... 3+ Coordination forms the first complex, wherein the β-cyclodextrin modified with thiolized diethylenetriamine is deprotonated and then reacts with Ag. + Coordination forms a second complex, and the first and second complexes thermally decompose at reflux temperature to release In. 3+ and Ag + The released In 3+ and Ag + With S 2- Based on the soft and hard acid-base theory and the LaMer nucleation and growth model, nucleation and growth occur. The β-cyclodextrin modified with thiolized diethylenetriamine is used as the only end-capped ligand to coat the surface of AgInS2 quantum dots, thereby obtaining an aqueous dispersion of AgInS2 quantum dots coated with β-cyclodextrin modified with thiolized diethylenetriamine. The AgInS2 quantum dot aqueous dispersion was subjected to precipitation separation, washing, and drying to obtain AgInS2 quantum dot powder. (2) The ethylene-vinyl acetate copolymer is dissolved in tetrahydrofuran and mixed with the aqueous dispersion of the AgInS2 quantum dot powder. The miscibility of tetrahydrofuran and water is used to make the AgInS2 quantum dots uniformly dispersed in the ethylene-vinyl acetate copolymer matrix. The solvent is removed, a film is formed and dried to obtain the light-converting agricultural film.

4. The preparation method according to claim 3, characterized in that, The reflux temperature is 100℃~120℃, and the AgNO3 aqueous solution and Na2S aqueous solution are injected and the reflux reaction continues for 20 min~60 min.

5. The preparation method according to claim 3, characterized in that, The molar ratio of AgNO3 to the β-cyclodextrin modified with thiolated diethylenetriamine is 1:4 to 1:

14.

6. The preparation method according to claim 3, characterized in that, The molar ratio of AgNO3 to InCl3 is 1:3 to 1:

5.

7. The preparation method according to claim 3, characterized in that, The precipitation separation includes adding the AgInS2 quantum dot aqueous dispersion to anhydrous ethanol to precipitate the precipitate, followed by centrifugation and washing the precipitate with acetone.

8. The preparation method according to claim 3, characterized in that, The mass ratio of the ethylene-vinyl acetate copolymer to the AgInS2 quantum dots is 10.6:1; the solvent removal is carried out by evaporation at room temperature for 18-36 hours, and the drying is carried out by vacuum drying at 40-60°C for 12-24 hours.

9. The application of the light-converting agricultural film according to claim 1 or 2 in facility agriculture, characterized in that, The light-converting agricultural film is used as a greenhouse covering for the cultivation of fruits and vegetables, including tomatoes, peppers, cucumbers, strawberries, radishes, bok choy, or corn.